Infrastructure's role in enhancing child well-being across sub-Saharan Africa - Kenmegne Audre Nikita; Tchounga Anatole; Ngueuleweu Tiwang Gildas (Sustainable Futures)
Even though several studies link access to infrastructure and wellbeing, very few clearly examine the impact of this relationship on children. so, does enhanced access to infrastructures improve child well-being? Thus, the study examines the contribution of access to infrastructure on children's well-being. It uses the Generalized Method of Moments (GMM) on 30 countries in sub-Saharan Africa from 2000 to 2020.. Results of the study show that access to education, healthcare, electricity and sanitation helps reduce child mortality and anemia. Thus, authorities in developing countries should Improve the construction and development of these infrastructures. Furthermore, public policies should ensure that infrastructures are accessible to all children, including those with special needs or living in rural or disadvantaged areas.